(untitled) (Journal of Partial Differential Equations, 1998)
In this paper we discuss the supersonic flow past a curved convex wedge. Our conclusion is that if the vertex angle of the wedge is less than a critical angle, the shock attached the head of the wedge is weak, and if the wedge is formed by a smooth convex curve, monotonically increasing, then the global solution of such a boundary value problem exists.